Ga]Ga-Pentixafor and Sodium [[sup.18]F]Fluoride PET Can Non-Invasively Identify and Monitor the Dynamics of Orthodontic Tooth Movement in Mouse Model - Craveiro, Rogerio B; Florea, Alexandru; Niederau, Christian; Brenji, Sihem; Kiessling, Fabian; Sahnoun, Sabri E. M; Morgenroth, Agnieszka; Mottaghy, Felix M; Wolf, Michael (Cells (Basel, Switzerland), 2022)
The cellular and molecular mechanisms of orthodontic tooth movement (OTM) are not yet fully understood, partly due to the lack of dynamical datasets within the same subject. Inflammation and calcification are two main processes during OTM. Given the high sensitivity and specificity of [[sup.68] Ga]Ga-Pentixafor and Sodium [[sup.18] F]Fluoride (Na[[sup.18] F]F) for inflammation and calcification, respectively, the aim of this study is to assess their ability to identify and monitor the dynamics of OTM in an established mouse model. To monitor the processes during OTM in real time, animals were scanned using a small animal PET/CT during week 1, 3, and 5 post-implantation, with [[sup.68] Ga]Ga-Pentixafor and Na[[sup.18] F]F. Both tracers showed an increased uptake in the region of interest compared to the control. For [[sup.68] Ga]Ga-Pentixafor, an increased uptake was observed within the 5-week trial, suggesting the continuous presence of inflammatory markers. Na[[sup.18] F]F showed an increased uptake during the trial, indicating an intensification of bone remodelling. Interim and end-of-experiment histological assessments visualised increased amounts of chemokine receptor CXCR4 and TRAP-positive cells in the periodontal ligament on the compression side. This approach establishes the first in vivo model for periodontal remodelling during OTM, which efficiently detects and monitors the intricate dynamics of periodontal ligament.